A new scoring system for the triage of cardiac tamponade. (March 2015) - Imazio, Massimo; Adler, Yehuda; Ristić, Arsen D; Charron, Philippe
<x xml:space="preserve">Abstract</x> Prompt recognition of cardiac tamponade is critical since the underlying hemodynamic disorder can lead to death if not resolved by percutaneous or surgical drainage of the pericardium. Nevertheless, the management of cardiac tamponade can be challenging because of the lack of the validated criteria for the risk stratification that should guide clinicians in the decision-making process. The Working Group on Myocardial and Pericardial Diseases issued this position statement in order to reply to specific questions: Which patients need immediate drainage of the pericardial effusion?; Is echocardiography sufficient for guidance of pericardiocentesis or should patient be taken to the cardiac catheterization laboratory?; Who should be transferred to specialized/tertiary institution or surgical service?; What type of medical support is necessary during transportation? Current European guidelines published in 2004 do not cover these issues and no additional guidelines are available from major medical and cardiology societies.